2014
DOI: 10.1063/1.4894690
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear instability of an Oldroyd elastico–viscous magnetic nanofluid saturated in a porous medium

Abstract: Through viscoelastic potential theory, a Kelvin-Helmholtz instability of two semi-infinite fluid layers, of Oldroydian viscoelastic magnetic nanofluids (MNF), is investigated. The system is saturated by porous medium through two semi-infinite fluid layers. The Oldroyd B model is utilized to describe the rheological behavior of viscoelastic MNF. The system is influenced by uniform oblique magnetic field that acts at the surface of separation. The model is used for the MNF incorporated the effects of uniform bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Hossain and Khan [20] showed that the flow became unstable owing to the presence of nanoparticles in a wall-driven flow through a tube, and flow instability was dependent on the particle concentration, the particle density, and the Reynolds number. Moatimid et al [21] studied the flow stability in a porous medium for the Oldroyd elastico-viscous magnetic fluid. Rudyak et al [22] found that the degree of destabilization was enhanced by an increase in the particle concentration and a decrease in the particle diameter in the pipe.…”
Section: Hydrodynamic Instabilitymentioning
confidence: 99%
“…Hossain and Khan [20] showed that the flow became unstable owing to the presence of nanoparticles in a wall-driven flow through a tube, and flow instability was dependent on the particle concentration, the particle density, and the Reynolds number. Moatimid et al [21] studied the flow stability in a porous medium for the Oldroyd elastico-viscous magnetic fluid. Rudyak et al [22] found that the degree of destabilization was enhanced by an increase in the particle concentration and a decrease in the particle diameter in the pipe.…”
Section: Hydrodynamic Instabilitymentioning
confidence: 99%
“…Our upcoming study will address these forms non-Newtonian models in consideration due to the practical applications of the various structures of non-Newtonian prototyping as progress works. Furthermore, particular linear stability non-Newtonian standards were explored along with our earlier articles 10 , 46 , 50 52 . Therefore, away from the simplified formulation of Hsieh’s formula 38 and[39[, the future works will adopt the energy as well as the concentration equations.…”
Section: Discussionmentioning
confidence: 99%